Train to Busan [videorecording (DVD)] - Kong, Yu, 1979-; Ch'oe, U-sik, 1990-; Chŏng, Yu-mi, 1983- (Well Go USA Entertainment, 2017)
While a zombie-virus breaks out in South Korea, a couple of passengers struggle to survive on the train from Seoul to Busan.